DESIGN AND IMPLEMENTATION OF WIRELESS SENSOR AND ACTUATOR FOR PLC BASED SCADA SYSTEM IN STANDARD WATER FILTRATION PROCESS - Agung, Albertus (Department of Electrical Engineering, University of Patria Artha, 2018)
This research aims to design and implement a cheap, low power and reliable wireless sensor and actuator system which can be used in the PLC based SCADA system to overcome the limitations of wire media. The wireless sensor and actuator system can also be used as an alternative to reduce the amount of the used PLC within SCADA system. Usually, in a PLC based SCADA system, sensor and actuator are connected to PLC with wire. It has many limitations especially in terms of flexibility and resistance to interference noise, In the PLC based SCADA system with wire media also causes the number of the installed PLC will increase at each location that will be monitored or controlled. This is not efficient if the location has only a few sensors or actuators that are connected to PLC because it will have an impact on the greater costs due to expensive price of the PLC. In this research already designed a wireless sensor and actuator system based on WPAN technology (IEEE 802.15.4) is cheap, low power and reliable. The results reveal that the wireless sensor and actuator system is able to send data with good accuracy and also able to operate well when implemented to PLC based SCADA system with open loop control and closed loop control to control the water level in the tub filtration. From the results, it can be concluded that the wireless sensor and actuator system can be used in the PLC based SCADA system to overcome the limitations of wire media and can also be used as an alternative to reduce the amount of the used PLC within SCADA system.